The importance of specific IgE antibodies in epidemiology of allergic rhinitis and asthma – the Epidemiology of Allergic Diseases in Poland (ECAP) survey: part one. Influence of allergy risk factors on concentration of specific IgE antibodies in serum - Namysłowski, Andrzej; Samoliński, Bolesław K.; Lipiec, Agnieszka; Zieliński, Wojciech; Sybilski, Adam J.; Walkiewicz, Artur; Samel-Kowalik, Piotr; Samoliński, Krzysztof; Raciborski, Filip (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2018)
Introduction: Specific immunoglobulins E (sIgE) are important parameters to estimate severity of allergic diseases. Aim : To determine the influence of allergy risk factors on the concentration of specific IgE antibodies in serum. Material and methods : The concentration of sIgE antibodies against allergens Dermatophagoides pteronyssinus , cat dander, timothy grass, Alternaria alternata were determined in serum of 4077 respondents randomly selected from 9 regions (ECAP study). The positive results of sIgE (≥ 0.35 IU/ml) were correlated to answers in questionnaires ECRHSII and ISAAC. Results : sIgE are more frequently detected in respondents declaring an allergic disease of a father than of a mother ( D. pteronyssinus p < 0.05, A. alternata p < 0.01). An early beginning to attend school, kindergarten or nursery increases the frequency of sIgE detection (p < 0.05). If the number of children who slept in the same room as a respondent before the respondent was five years old, was lower, sIgE antibodies are more frequently detected (p < 0.05). Relating to: 1) all 4 allergens, sIgE are the most frequently detected in respondents declaring absence of a carpet/rug at home (p < 0.05), 2) cat dander – less frequently detected in respondents who have a cat at home at the age of 1–4 years (p < 0.005). Conclusions : Carpets/rugs capture a portion of mite, epidermal, mould allergens located at home, wherefore absence of a carpet or rug causes greater stimulation of an immune system by these allergens; as a consequence, IgE antibodies are the most frequently detected in respondents. Household contacts of the respondents, at the age of 1–4 years, with cats induced partial immune tolerance to cat dander.